THE INFLUENCE OF STUDENTS' ACTIVITIES ON TEACHERS' QUESTIONS IN CLASSROOM LANGUAGE LEARNING :Case Study of Four Language Teachers at Two English Courses in Bandung, West Java - Jusnita, Naniek (2011)
Classroom activities that have been designed before hand besides facilitate language learning/acquisition may also influence teachers' questioning. Based on that reason, this study is to investigate (1) kinds of classroom activities that contribute to the types of teachers' questions, (2) students' responses on different types of teachers' questions, and (3) teachers' questions that facilitate language learning. This study employed qualitative case study. The setting was two English courses in Bandung with four teachers and 45 students in four classes as participants. The data of this research were collected through non-participant observation with video recording, field notes and interviews. The data were analyzed through thematic data analysis and presented one by one on the basis of the research questions. The result showed that teachers had implemented the different kinds of classroom activities such whole-class, groupwork and pairwork, individual-work, games, TPR and role-play. From the implementation of those kind of classroom activities, different types of teachers' questions had been identified such as display question, referential question, clarification request, comprehension check and confirmation check. Mostly the four teachers were used display question in presenting the topics, and students' books were used to create the questions. Students' verbal responses were characterized as restricted and elaborated response, while students' non-verbal responses were shown by nodding, smiling, laughing, acting and hesitating. Referential question facilitated students to use his /her cognitive in elaborating the answers, produces more quality utterances and provide interactions. Display question facilitated students to understand the reading-story, to scaffold the students in understanding the content of reading-story, increase the quantity of interaction, achieve immediate fedback and facilitate students' initiation. In confirmation check, comprehension check and clarification request, faciliated students to provide negotiation, build the interaction and motivate the students in learning. In conclusion, the discrepancy of using different type of questions in certain classroom activity is caused by the materials of teaching. The use of students' book facilitate the teacher to use more display questions. Thus, teachers' questions play very important rule in facilitating classroom language learning. It can provide comprehensible inputs, facilitate interaction, and trigger the students to use the target language as the medium of practicing the target language. For that reason, teachers' modification on types of questions are very recommended to elaborate during the teaching process in classroom activity.